Lippia alba—a potential bioresource for the management of Spodoptera frugiperda (Lepidoptera: Noctuidae) - Biswas, Shreosi; Kundu, Aditi; Suby, S. B.; Kushwah, Abran Singh; Patanjali, Neeraj; Shasany, Ajit Kumar; Verma, Rajesh; Saha, Supradip; Mandal, Abhishek; Banerjee, Tirthankar; Kumar, Anil; Singh, Anupama (Frontiers in Plant Science, 2024)
Fall armyworm (FAW), Spodoptera frugiperda (J.E. Smith), a threat to maize production systems, is a polyphagous pest of global significance. There is no registered bioinsecticide of botanical origin to provide green remedy against this pest of concern. The present study reports for the first time the potency of the polar and non-polar bioinsecticidal leads sourced from Lippia alba (Mill.) N.E. Br. leaves. Shade-dried leaves of L. alba were extracted and evaluated; based on preliminary bioassay, the ethyl acetate leaf extract of L. alba (LEAE) was found to be the most potent against FAW in the in vitro and in vivo studies. Ultraperformance liquid chromatography–quadrupole time-of-flight–mass spectrometric (UPLC-QToF-MS) analysis of LEAE revealed the rich chemical profile of 28 compounds, dominated by flavones, namely, naringenin, trihydroxy-dimethoxy flavone, and dihydroxy-trimethoxy flavone. Among others, glycosides, such as clerodendrin, calceolarioside E, forsythoside B, geniposide, and martynoside, and glucuronides, such as luteolin-7-diglucuronide, tricin-7-O-glucuronide, and luteolin-7-O-glucuronide, were also identified. LEAE exhibited exceptionally high in vitro [LC50 = 6,900 parts per million (ppm)] and in vivo (computed as damage score on a scale of 1–9) insecticidal activity against S. frugiperda, with no phytotoxicity at a dose as high as 20 times of LC50. LEAE also exhibited significant antifeedant, ovicidal, and growth regulatory activity at the 70–16,000 ppm (w/v) concentration range. In silico assessment revealed strong binding of martynoside, calceolarioside E, and forsythoside B with acetylcholinesterase-, sodium-, and chloride-dependent γ-aminobutyric acid (GABA) receptor and ryanodine receptor, respectively, facilitated by hydrogen bonds (conventional and C–H bonds) stabilized by hydrophobic pi–sigma, pi–pi stacked, pi–alkyl, and alkyl interactions. The present study established L. alba as a potential bioresource and secondary metabolite enriched LEAE as bioinsecticide for further product development.